PERAN PEMEDIASIAN MOTIVASI TERHADAP PENGARUH KARAKTERISTIK INTI PEKERJAAN DAN EFIKASI DIRI PADA KEPUASAN KERJA PEBISNIS ONLINE DI KOTA JAMBI - Nur Hasanah; Novita Eka Sari (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study proposes a mechanism to explain the effect of core job characteristics and selfefficacy on job satisfaction of online businesses in the city of Jambi. Previous research indicates that there are motivational factors that contribute to explaining the mechanism. This study aims to examine the effect of core job characteristics and self-efficacy positively and directly on job satisfaction. In addition, this study also aims to examine the effects of motivation mediation on the influence of core job characteristics and self-efficacy on job satisfaction. The study was conducted by survey method, with the research instrument in the form of an online questionnaire. A sample of 100 online business people in the city of Jambi. The data collection method is carried out by distributing questionnaires to respondents who are online businesses with various types of business. The unit of analysis in this study is the individual. The method of data analysis uses Structural Equation Modeling (SEM) with the help of AMOS 22.0 software. The results showed that motivation partially mediates the effect of core job characteristics and self-efficacy on job satisfaction of online businesses in the city of Jambi.